2022
DOI: 10.1021/acsenergylett.2c00157
|View full text |Cite
|
Sign up to set email alerts
|

Memory Effect in Lithium Titanate Driven by Interfacial Oxygen Vacancies

Abstract: Memory effect is undesirable abnormal voltage behavior in batteries that appears as a result of certain usage history. Al-doped Li 4 Ti 5 O 12 (LTO), LiFePO 4 , and TiO 2 that undergo phase transformations during lithiation/delithiation are known to possess a memory effect. Memory effect in these materials typically arises because of delayed onset of potential overshoot at the beginning of the delithiation voltage profile. In general, memory effect is associated with the sluggish electrochemical kinetics of ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…EIS analysis was employed to further investigate the interfacial charge transfer processes. The Nyquist spectra of the TNO samples (Figure A–C) showed three semicircles and a low-frequency capacitive tail, which is a common observation in Li-ion storage materials. The first semicircle in the high-frequency region is attributed to the charge-transfer resistance through the SEI layer ( R SEI ). The second semicircle originates from the interfacial charge-transfer resistance at the electrolyte/particle interface ( R ct ).…”
Section: Resultsmentioning
confidence: 87%
“…EIS analysis was employed to further investigate the interfacial charge transfer processes. The Nyquist spectra of the TNO samples (Figure A–C) showed three semicircles and a low-frequency capacitive tail, which is a common observation in Li-ion storage materials. The first semicircle in the high-frequency region is attributed to the charge-transfer resistance through the SEI layer ( R SEI ). The second semicircle originates from the interfacial charge-transfer resistance at the electrolyte/particle interface ( R ct ).…”
Section: Resultsmentioning
confidence: 87%
“…88 The defects or vacancies of metal atoms depend on their paramagnetic transition intensities, which can be represented with a constant parameter ‘ g. ’ The paramagnetic transition at g = 2.003 manifests the presence of OVs in the materials in EPR measurement. 89–91 For example, Wang et al reported mesoporous NiCo 2 O 4 and Co 3 O 4 microspheres by a facile synthesis strategy and subjected them to a partial reduction. The intrinsic behavior and corresponding surface area of the microspheres in the above spinel materials were enhanced as the reduction progressed.…”
Section: Characterization Of Ovs In Bimetallic Spinel and Perovskite ...mentioning
confidence: 99%
“…[1][2][3][4] Lithium-ion batteries (LIBs) are in enormous demand in many applications such as vehicle transportation, stationary energy storage, portable electronics, and large-scale energy systems. [5][6][7][8][9][10][11][12][13][14][15] The attractive applications of LIBs are mainly due to their superior energy density and longer service life, [16][17][18][19][20][21] and these properties are dependent on the electrochemical performance of the cathode electrode material. [22][23][24] The cathode electrode design must account for material cost, safety, and structural stability capabilities, and it can be used to create promising high-performance LIBs.…”
Section: Introductionmentioning
confidence: 99%